An 8-week neuromuscular training program after concussion reduces 1-year subsequent injury risk: A randomized clinical trial - Howell, D. R.; Seehusen, C. N.; Carry, P. M.; Walker, G. A.; Reinking, S. E.; Wilson, J. C. (The American Journal of Sports Medicine, 2022)
Background: Existing data suggest that after concussion, athletes experience an increased risk of subsequent injury. Exploring methods that may reduce injury risk after successful postconcussion return to play may lead to new treatment approaches.